Determining the Effectiveness of Micronutrients in the Management of Oral Submucous Fibrosis - Nidhi Thakur; Rohit Sharma; Uday Narayan Sharma; Mysore K Sunil; Sunil Sharma; Niharika Sharma; Aayushi Pakhale (Journal of Pharmacy and Bioallied Sciences)
Background: Oral submucous fibrosis (OSMF) is a chronic, progressive, and potentially malignant disorder primarily caused by areca nut and tobacco consumption. This study aimed to evaluate the effectiveness of micronutrient supplementation in improving mouth opening and alleviating symptoms in OSMF patients. Materials and Methods: A total of 50 clinically diagnosed OSMF patients were included in this interventional study. All participants received daily micronutrient supplements containing essential vitamins and minerals. The primary outcome measure was mouth opening (interincisal distance), recorded at baseline, one month, three months, and six months. Secondary outcomes included pain reduction (VAS score), intolerance to spices, burning sensation, and ulceration. Statistical analysis was performed using SPSS software, with P < 0.05 considered significant. Results: The mean mouth opening significantly increased from 21.00 mm at baseline to 28.60 mm at six months (P < 0.01), indicating a reduction in fibrosis and improved oral mobility. The VAS pain score decreased from moderate to mild pain, demonstrating symptomatic relief. Additionally, intolerance to spices reduced from 96% to 48%, the burning sensation declined from 54% to 26%, and ulceration was completely resolved in the micronutrient group. Conclusion: Micronutrient supplementation is an effective, noninvasive, and cost-efficient approach for the management of early-stage OSMF. It significantly improves mouth opening, reduces pain, and alleviates symptoms. Given these benefits, micronutrient therapy should be considered a first-line treatment for OSMF. Further long-term studies are needed to establish standardized protocols for its use.